1985
DOI: 10.1007/bf01200801
|View full text |Cite
|
Sign up to set email alerts
|

Differential proliferative responses of cultured Schwann cells to axolemma and myelin-enriched fractions. II. Morphological studies

Abstract: Axolemma-enriched and myelin-enriched fractions were prepared from bovine CNS white matter and conjugated to fluorescein isothiocyanate (FITC). Both unlabelled and FITC-labelled axolemma and myelin were mitogenic for cultured rat Schwann cells. Treatment of Schwann cells with the FITC-labelled mitogens for up to 24 h resulted in two distinct morphological appearances. FITC-myelin-treated cells were filled with numerous round, fluorescent-labelled intracellular vesicles, while FITC-axolemma-treated cells appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…These results are in agreement with previous observations that used a fluorescein-conjugated myelin fraction (9). Despite the presence of immunoreactive material in almost every Schwann cell, only 1% of the cells treated with the myelin-enriched fraction for 24 h were labeled [3n]thymidine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with previous observations that used a fluorescein-conjugated myelin fraction (9). Despite the presence of immunoreactive material in almost every Schwann cell, only 1% of the cells treated with the myelin-enriched fraction for 24 h were labeled [3n]thymidine.…”
Section: Discussionsupporting
confidence: 93%
“…Primary cultures of Schwann cells were prepared as described by Brockes et al (5) and modified by Meador-Woodruff et al (9). Briefly, the sciatic nerves of 2-d-old rat pups were excised, treated with collagenase and trypsin, and plated in 10-cm glass petri dishes in HF media.…”
Section: Preparation Of Cultured Schwann Cellsmentioning
confidence: 99%
“…Cultured peritoneal macrophages that had been treated with MEF for 24 or 48 hr were fixed and processed for electron microscopy as described (17). RESULTS…”
Section: Methodsmentioning
confidence: 99%
“…Much evidence has shown that the digestive process of myelin is intimately related to Schwann cell proliferation (1,2,5,8,11,20,21). The removal of the myelin sheath elicited proliferative response of Schwann cells (5,12,16).…”
mentioning
confidence: 99%